Atlas of pain management injection techniques - Waldman, Steven D. (Elsevier/Saunders, 2013)
Provides an essential pain management injection technique. From head and neck to foot and ankle - and everywhere between - this title equips you to perform a range of clinical injection techniques with greater confidence.